Temporal genome-wide DNA methylation signature of post-smolt Pacific salmon challenged with Piscirickettsia salmonis. Issue 12 (2nd December 2021) - Leiva, Francisco; Bravo, Scarlet; Garcia, Killen Ko; Moya, Javier; Guzman, Osiel; Bascuñan, Nicolás; Vidal, Rodrigo
ABSTRACT: Piscirickettsiosis is the most important bacterial disease in the Chilean salmon industry, which has sorted several efforts to its control, generating enormous economic losses. Epigenetic alterations, such as DNA methylation, can play a relevant role in the modulation of the metazoans response to pathogens. Bacterial disease may activate global and local immune responses generating intricate responses with significant biological impact in the host. However, it is scarcely understood how bacterial infections influence fish epigenetic alterations. In the present study, we utilized Pacific salmon and Piscirickettsiosis as model, to gain understanding into the dynamics of DNA methylation among fish-bacterial infection interactions. A genome-wide analysis of DNA methylation patterns in female spleen tissue of Pacific salmon was achieved by reduced representation bisulphite sequencing from a time course design. We determined 2, 251, 1, 918, and 2, 516 differentially methylated regions DMRs among infected and control Pacific salmon in 1 dpi, 5 dpi, and 15 dpi, respectively. The mean methylation difference per DMR among control and infected groups was of 35%, with an oscillatory pattern of hypo, hyper, and hypomethylation across the disease. DMCs, among the control and infected group, showed that they were statistically enriched in intergenic regions and depleted in exons. Functional annotation of the DMR genes demonstrated three KEGG principal categories, associated directly with the host response to pathogens infections. Our results provide the first evidence of epigenetic variation in fish provoked by bacterial infection and demonstrate that this variation can be modulated across the disease.